2019
DOI: 10.1080/00015385.2019.1570675
|View full text |Cite
|
Sign up to set email alerts
|

The role of cardiac rehabilitation in vocational reintegration Belgian working group of cardiovascular prevention and rehabilitation position paper

Abstract: Cardiovascular disease is one of the main causes of morbidity and sick leave in Belgium, imposing a great socioeconomic burden on the contemporary healthcare system and society. Cardiac rehabilitation is an evidence-based treatment strategy, that not only improves the cardiac patients' health state but also holds promise as to facilitate vocational reintegration in society. This position paper was developed and endorsed by the Belgian Working Group of Cardiovascular Prevention & Rehabilitation. It provides an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…Rather, it has been shown to be related to the same demographic factors that were found to be positively related to return-to-work in the literature: male gender, married status, longer tenure, low intensity of physical effort, and higher income prior to the cardiac event. 3,7 Moreover, our study shows that negative psychological factors turned out to be determinants of the detachment from employment at one-and two years of follow-up: negative expectations concerning return-to-work, daily functioning, and depressive symptoms, all congruent with the findings of other studies. 8,16,29,30 Nonetheless, the intervention programs proved to be a powerful determinant of long-term employment over and above the demographic, occupational, and psychological factors.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Rather, it has been shown to be related to the same demographic factors that were found to be positively related to return-to-work in the literature: male gender, married status, longer tenure, low intensity of physical effort, and higher income prior to the cardiac event. 3,7 Moreover, our study shows that negative psychological factors turned out to be determinants of the detachment from employment at one-and two years of follow-up: negative expectations concerning return-to-work, daily functioning, and depressive symptoms, all congruent with the findings of other studies. 8,16,29,30 Nonetheless, the intervention programs proved to be a powerful determinant of long-term employment over and above the demographic, occupational, and psychological factors.…”
Section: Discussionsupporting
confidence: 89%
“…4,6,26 The success of the comprehensive case-management program in facilitating long-term maintenance of employment may be explained, in addition to the factors mentioned above, by containing other components of disability management/vocational rehabilitation programs, suggested by rehabilitation specialists as important for enhancing work re-integration, namely: occupational counseling, monitoring and providing support and alleviating any difficulties during work reintegration, addressing personal and work related-obstacles that might affect an individual's decision to return-to-work, and providing coordination between all relevant parties. 6,7,27,28 The majority of the participants in this study participated in a regular cardiac rehab program (see Methods). However, the findings here showed that rehab participation had no effect on employment status either at one year or two years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients can usually also return to work after a period of cardiac rehabilitation. 3 However, a significant proportion of ACS patients may experience problems in the process of returning to work.…”
mentioning
confidence: 99%
“…Also, patients in a cardiac rehabilitation programme return to work earlier and are less often taking up easier or lighter work. 3,5 There is, however, still plenty of room for improvement in including eligible patients in cardiac rehabilitation, as well as for the content of cardiac rehabilitation programmes themselves as these programmes often focus on the underlying cardiac disease and pay little or no attention to workrelated factors or even RTW. Clear advice concerning RTW should be present in every cardiac rehabilitation programme for patients of working age.…”
mentioning
confidence: 99%